Nesting ecology of stingless bees within three landscapes in the Northern part of the Volta Region of Ghana - Tornyie, Ferdinand (University of Cape Coast, 2013)
This research was carried out to investigate the nesting ecology of stingless bees in three selected landscapes in the northern part of the Volta Region of Ghana, from June 2011 to February 2012. The study focused on three stingless bee species Meliponula bocandei (Spinola), Meliponula ferruginea (Lepeletier) and Dactylurina staudingeri (Gribodo). Using eight transects (500 X 40 m) in each landscape, number of nests, nesting heights, diameter at breast heights (DBH) of nest trees and potential nest trees were sampled at three sites namely Koru, Abotoase and Kyabobo. Out of a total of 93 stingless bee nests found, M. ferruginea recorded the highest (50) compared to M. bocandei (33) and D. staudingeri (10). Nest density for the three sites was estimated to be 1.9 nests/ha (≈ 2 nests/ha). M. ferruginea was the only species that nested in old termite mounds (17 nests) and in the ground (1 nest). The bees did not show preference for particular tree species they nest in. The two Meliponula bee species were found nesting in trees with DBH ≥15 cm. Landscape characteristics appeared to have some effects on the nesting ecology of stingless bees. Koru, which recorded larger trees had the highest nest density. Less suitable nesting trees in Abotoase influenced M. ferruginea to nest more in old termite mounds than trees. Extraction of potential nesting trees due Agricultural activities and wild honey hunting are threats to stingless bee colonies in Koru and Abotoase. Lack of more suitable nesting trees could account for lower stingless bee nests in Kyabobo National Park.
xiii,144p.:ill